Design, Development, and Characterization of Modified Xanthan Gum Based Novel in situ Gel of Ciprofloxacin Hydrochloride for Ophthalmic Drug Delivery - Jadhav, Dr. Rahul Laxman (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: Ciprofloxacin hydrochloride is a broad-spectrum a powerful fourth generation fluoroquinolone antibiotic active against both Gram-positive and Gram-negative ocular pathogens such as Pseudomonas aeruginosa and Staphylococcus aureus and used the treatment of ocular infections. In conventional dosage forms its washout, poor retention, drainage from eyes affects its therapeutic efficiency, so there is need of novel formulation of it. The aim and objectives of this research work are to explore the applicability of our previously modified xanthan gum in formulation, optimization, and evaluation of in situ gel of ciprofloxacin hydrochloride for ophthalmic drug delivery. Materials and Methods: Fourier-transform infrared (FT-IR) and differential scanning calorimetry (DSC) study was performed to find out compatibilities between drug and polymers. To find out the impact of Conc. of Modified Xanthan Gum …(X1) and… HPMC (X2) on dependent variables, i.e., gelation temperature and viscosity 32 factorial designs Optimization technique was used. In situ gel was prepared using modified xanthan gum and HPMC, etc. The prepared in situ gel of ciprofloxacin was evaluated for pH, gelation time, gelation temperature, viscosity, drug content, syringeability, antimicrobial potential, and in vitro drug release. Results and Discussion: FT-IR and DSC study suggests no interaction between ciprofloxacin, modified xanthan gum, and HPMC. The pH of in situ gel solution was found to be around 6.6 ± 0.2–6.9 ± 0.08 which is an acceptable range for ophthalmic preparations. Gelation time of prepared in situ gel solution was found to be around 10.6 ± 1.2–32 ± 0.8 s. Gelation temperature of prepared in situ gel batches was found to be around 30.6 ± 0.4–35 ± 0.8°C. It was found that increasing the concentration of the polymer resulted in a significant increase in viscosity. Modified xanthan gum had a more pronounced effect on the viscosity than HPMC at the studied ranges. In vitro, drug release studies showed a polymer concentration-dependent decrease in drug release. Formulation F8 selected as an optimized batch has maximum gelling temperature 34.6 ± 1.2°C and minimum drug release 91.59% drug release. Optimized formulation gave satisfactory results in terms of antimicrobial activity. The optimization study was successfully conducted using 32 factorial designs. Conclusion: Developed in situ gelling systems are viable alternative to conventional ophthalmic products with added ben efits of sustained drug released and it will promising approach toward the treatment of various bacterial infections.